Electropositive heterogeneous film as well as preparation and application thereof

By combining the positive electrostatic SAMM film formed by self-assembly of UiO-66-NH2 nanoparticles coated with functional polymers with porous AAO membrane, an efficient heterogeneous membrane was prepared, which solved the penetration energy collection process of existing ion exchange membranes. The problem of insufficient performance has achieved the penetration energy collection effect of high output power.

CN119425396AActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310938837.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

During the osmotic energy collection process, existing ion exchange membranes have limitations such as poor ion selectivity, insufficient mass transfer and large membrane resistance, resulting in lower output power.

Method used

A highly efficient heterogeneous membrane was prepared by combining a positively charged SAMM film formed by self-assemblying the functional polymer-coated UiO-66-NH2 nanoparticles at the water-air interface with a porous AAO membrane.

Benefits of technology

A maximum output power of 2.99W/m2 was achieved at a 50-fold NaCl gradient, significantly improving the performance of osmotic energy collection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004364467920000011
    Figure HDA0004364467920000011
  • Figure HDA0004364467920000012
    Figure HDA0004364467920000012
  • Figure HDA0004364467920000021
    Figure HDA0004364467920000021
Patent Text Reader

Abstract

The invention relates to preparation and application of a heterogeneous film consisting of an electropositive metal organic framework (MOF) monolayer film and a porous anodic aluminum oxide (AAO) film. The method comprises the following steps: grafting a macromolecular chain transfer agent to the surfaces of MOF particles through modification after synthesis; the method comprises the following steps: grafting a polymer to the surfaces of MOF particles by initiating a reversible addition-fragmentation chain transfer polymerization reaction on the surfaces of methyl methacrylate and 1-vinyl imidazole; the MOF particles are self-assembled on a water-air interface to form a compact MOF monolayer (SAMM) membrane; and covering one side of the AAO membrane with the prepared SAMM membrane to form a heterogeneous membrane, and detecting the permeation energy collection performance of the heterogeneous membrane. The invention realizes the first application of the SAMM membrane in the field of osmotic energy collection, and provides a new method for preparing an ion exchange membrane material with high ion selectivity and permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material chemistry, and specifically to a preparation method of a heterogeneous membrane formed by combining a positively charged self-assembled MOF monolayer (SAMM) membrane formed by self-assembly of metal organic framework (MOF) nanoparticles coated with a functional polymer and a porous anodic aluminum oxide (AAO) membrane, and its application in the field of osmotic energy collection. Background Art

[0002] Against the backdrop of the continuous consumption of fossil fuels and the increasing demand for energy, the development of sustainable and environmentally friendly energy has become a research hotspot. Osmotic energy, also known as salinity gradient energy, is energy generated by utilizing the salinity difference between seawater and river water. It is widely regarded as an important blue energy source because of its easy access and abundant reserves. Reverse electrodialysis (RED) is a process that directly obtains energy from salinity gradients through ion-selective membranes, so it has great potential in harvesting osmotic energy. However, conventional ion exchange membranes used in the RED process have limitations such as poor ion selectivity, insufficient mass transfer, and high membrane resistance, resulting in low output power. To improve the performance of osmotic energy harvesting, researchers have developed two-dimensional (2D) nanofluidic channels, such as graphene, molybdenum disulfide (MoS2), MXene, boron nitride, and black phosphorus. These nanochannels can facilitate efficient ion transport in the planar direction. However, their poor performance in the transmembrane direction makes such 2D nanofluidic channels impractical for osmotic energy conversion applications. Recently, membranes containing single nanopores, such as single boron nitride nanotubes, single MoS2 nanopores, and single polyethylene terephthalate / polyimide nanopores, have brought energy density to a new level. However, it is very difficult to prepare such membranes on a macroscopic scale.

[0003] MOF is a special type of porous crystalline material with narrow ordered channel distribution, high specific surface area and customizable surface properties. It has become a promising material for energy and environment. The three-dimensional interconnected sub-nanoscale channels give MOF-based membrane materials great hope for breakthroughs in achieving high ion selectivity and permeability. However, despite these advantages of MOF, there is still a lack of simple, mild and flexible methods for preparing dense, crack-free, ultra-thin MOF films.

[0004] The SAMM membrane was first proposed by Cohen's research group in 2019. It is formed by the self-assembly of MOF nanoparticles. It is a dense, highly ordered, large-area, independent single-layer film with nanoscale thickness and extremely high MOF loading. This SAMM membrane maintains the characteristics of MOF materials and exhibits a shorter mass transfer path due to its ultra-thin thickness. Therefore, it circumvents the "permeability-selectivity" trade-off and shows broad application potential in the field of osmotic energy harvesting. Although several SAMM membranes have been reported, the fragility of these films prevents them from being further processed, and the lack of functional groups on the films hinders their practical application. In addition, functional modification of the SAMM membrane is likely to destroy its dense structure, resulting in large defects in the film. Therefore, it is still a huge challenge to prepare functionalized SAMM membranes and promote their practical applications while ensuring the integrity of the SAMM membrane. Summary of the invention

[0005] The present invention aims to design and prepare a positively charged heterogeneous membrane, and the method adopted is to cover the SAMM membrane formed by self-assembly of UiO-66-NH2 nanoparticles coated with functional polymers at the water-air interface on one side of the porous AAO membrane to prepare the positively charged heterogeneous membrane. The SAMM membrane prepared by the present invention is a large-area, dense, and extremely thin film. The heterogeneous membrane formed by combining with the AAO membrane has high ion selectivity and permeability, and provides a new solution for preparing other functional SAMM membranes.

[0006] Another object of the present invention is to provide an application scheme of the above-mentioned positively charged heterogeneous membrane in the field of osmotic energy collection. The method adopted is to fix the heterogeneous membrane on a homemade electrochemical device, apply voltage through Ag / AgCl electrodes, and then use a picoammeter to record the current. This heterogeneous membrane achieved 2.99W / m under a 50-fold NaCl gradient. 2 The maximum output power provides a new idea for the preparation of new ion exchange membranes with high permeability energy collection performance.

[0007] The object of the present invention is achieved by the following scheme:

[0008] A positively charged heterogeneous membrane, characterized in that the SAMM membrane formed by MOF particles modified by functional polymers at the water-air interface is transferred to the surface of a porous AAO membrane to prepare the heterogeneous membrane. The specific steps are as follows:

[0009] (1) Preparation of monodisperse UiO-66-NH2 nanoparticles: ZrCl4, 2-aminoterephthalic acid and 45 mL DMF were mixed in a container. The mixture was ultrasonicated for 15 min until the solid was completely dissolved. Then, glacial acetic acid was added to the above mixed solution, wherein the reagent molar ratio was ZrCl4:2-aminoterephthalic acid:glacial acetic acid = 1:1:30. After the mixture was stirred for 15 min, it was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in an oven at a constant temperature of 120°C for 24 h. After the reaction was completed, the reactor was allowed to cool naturally to room temperature and then opened. The product was centrifuged (8000 rpm, 10 min), and the obtained solid was washed with DMF and methanol in turn. The washed solid was placed in a vacuum drying oven set at a temperature of 40°C and dried for 12 h to obtain the product UiO-66-NH2.

[0010] (2) Preparation of macromolecular chain transfer agent (cat-CTA): 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid, N-hydroxysuccinimide and 40 mL of dry dichloromethane were mixed in a reaction flask. The reaction flask was placed in an ice-water bath and stirred for 60 min, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide was added, wherein the molar ratio of the reagents was 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid: N-hydroxysuccinimide: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide = 1:1.5:1.6, and then the mixture was stirred at room temperature for 12 h. After the reaction was completed, the product was washed with dilute hydrochloric acid, saturated NaHCO3 and deionized water in sequence, and the product in the aqueous solution was extracted with dichloromethane, and then the dichloromethane solution was dried over anhydrous MgSO4 for 20 min. The dried solution was filtered and concentrated, and the crude product was purified by silica gel column, with the eluent being a mixed solution of petroleum ether and ethyl acetate in a volume ratio of 2:1.

[0011] The above pure product (NSH-CTA), dopamine hydrochloride and 40mL dry tetrahydrofuran were mixed in a reaction bottle. After the reaction bottle was placed in an ice-water bath and stirred for 60 minutes, triethylamine was added, wherein the molar ratio of the reagents was NSH-CTA: dopamine hydrochloride: triethylamine = 1: 1.1: 1.1, and then the mixture was stirred at room temperature for 12 hours. After the reaction was completed, the solvent was dried by rotary evaporator, the crude product was dissolved with dichloromethane, the product was washed with dilute hydrochloric acid and deionized water in turn, the product in the aqueous solution was extracted with dichloromethane, and then the dichloromethane solution was dried with anhydrous MgSO4 for 20 minutes. The dried solution was filtered and concentrated, and the crude product was purified by silica gel column, and the eluent was a mixed solution of petroleum ether and ethyl acetate with a volume ratio of 1: 1. The purified product was placed in a vacuum drying oven set at 40°C and dried for 12 hours to obtain the product cat-CTA.

[0012] (3) Preparation of macromolecular chain transfer agent modified UiO-66-NH2 (UiO-66-NH2-CTA): UiO-66-NH2, cat-CTA and DMF were mixed in a reaction bottle, wherein the molar ratio of the reagents was UiO-66-NH2: cat-CTA = 1:6, and the mixture was ultrasonicated for 30 min until the solid was completely dispersed. Then the reaction bottle was placed in an oil bath at a constant temperature of 100°C for 4 h. After the reaction was completed, the product was cooled to room temperature and centrifuged (8000 rpm, 10 min). The obtained solid was washed with DMF and methanol in turn and then dried in a vacuum drying oven set at 40°C for 12 h to obtain the product UiO-66-NH2-CTA.

[0013] (4) Polymer-coated U iO-66-NH2 (U iO-66-NH2-P (MMA 0.99 -co-VIM 0.01 )) Preparation: UiO-66-NH2-CTA and DMF were mixed in a container, followed by the addition of methyl methacrylate (MMA), 1-vinylimidazole (VIM) and 2,2'-azobisisobutyronitrile (AIBN), wherein the molar ratio of the reagents was CTA:MMA:VIM:AIBN = 1:40000:400:1. The mixture was frozen with liquid nitrogen for 15 minutes, evacuated with an oil pump for 5 minutes, and then thawed naturally at room temperature; after the above freezing-evacuation-thawing operation was cycled 3 times, the mixture was placed in an oil bath pot at a constant temperature of 70°C for 24 hours. After the reaction was completed, the crude product was centrifuged (8000rpm, 10min), and the obtained solid was washed with DMF and then washed with toluene. The product was dried in a vacuum drying oven set at 60°C for 12 hours to obtain the product UiO-66-NH2-P (MMA 0.99 -co-VIM 0.01 ).

[0014] (5) 50 mg UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) nanoparticles were mixed with 1 mL of toluene in a small glass bottle, and then ultrasonicated for 40 min; 10 μL of the above MOF solution was dropped into a petri dish with a diameter of 35 mm and a water depth of 1 cm. After being placed at room temperature for 3 min, the toluene was completely evaporated and a SAMM film was formed on the water surface. The porous AAO membrane (pore size range of 20-30 nm, pore density of about 1.0×10 12 pores / cm 2) was immersed in the water below the SAMM membrane, and the AAO side was slowly moved toward the water surface in a direction parallel to the water surface until the SAMM completely covered the AAO membrane, thus forming a composite membrane. The composite membrane was placed in a covered petri dish and dried at room temperature for 24 hours to form a heterogeneous membrane.

[0015] The present invention proposes an application scheme of a positively charged heterogeneous membrane in the field of osmotic energy collection, and the specific steps are as follows:

[0016] The heterogeneous membrane is connected with a central hole with an area of ​​0.004 mm 2 The silicon wafer was fixed together between the two modules of the homemade electrochemical device, 1 mL of 500 mM NaCl solution was added to the flow channel on one side of the SAMM, and 1 mL of 10 mM NaCl solution was added to the flow channel on one side of the silicon wafer. An Ag / AgCl electrode was inserted into the electrolyte solutions on both sides, voltage was applied through the electrodes, and the current was recorded using a picoammeter.

[0017] The method adopted by the present invention is as follows: cat-CTA is grafted onto the surface of U iO-66-NH2 particles through post-synthesis modification; a functional polymer is grafted onto the surface of U iO-66-NH2 particles through a surface-induced reversible addition-fragmentation chain transfer reaction of MMA and VIM; MOF particles coated with the functional polymer self-assemble at a water-air interface to form a dense SAMM membrane; the prepared SAMM membrane is covered on one side of a porous AAO membrane to form a heterogeneous membrane, and the permeation energy collection performance of the heterogeneous membrane is detected.

[0018] The present invention not only provides a new method for preparing large-area, dense, and extremely thin functionalized MOF monolayer membranes, but also provides a new idea for preparing ion exchange membrane materials for efficient osmotic energy collection.

[0019] The present invention realizes the first application of SAMM membrane in the field of osmotic energy collection and provides a new method for preparing ion exchange membrane materials with high ion selectivity and permeability.

[0020] The beneficial effects of the present invention are:

[0021] (1) The positively charged MOF monolayer membrane prepared by the present invention through water-air interface technology provides a new solution for preparing functional MOF monolayer membranes;

[0022] (2) The present invention combines the prepared positively charged MOF monolayer membrane with the porous AAO membrane to prepare a positively charged heterogeneous membrane, which provides a new idea for preparing a new type of ion exchange membrane material with high efficiency in osmotic energy collection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 SEM image of monodispersed UiO-66-NH2 nanoparticles;

[0025] Figure 2 For cat-CTA 1 H NMR spectrum;

[0026] Figure 3 UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) Acid hydrolysis products 1 H NMR spectrum;

[0027] Figure 4 is the cross-sectional SEM image of the SAMM membrane;

[0028] Figure 5 SEM images of AAO substrate (a) and heterogeneous membrane (b, c);

[0029] Figure 6 The collected current density (indicated by open symbols) and power density (indicated by solid symbols) of the heterogeneous membrane under 50 times NaCl gradient;

[0030] Figure 7 This is a schematic diagram of the current test device module.

[0031] Figure 8 It is a schematic diagram of the film making process and the testing process of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below.

[0033] 4-Cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid (97%) was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. N-hydroxysuccinimide (98%), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, ZrCl4 (98%), dopamine hydrochloride (98%), 2-aminoterephthalic acid (98%), VIM (99%) and AIBN (98%) were purchased from Aladdin Reagent (Shanghai) Co., Ltd. MMA (99%) was purchased from Alfa Aesar (China) Chemical Co., Ltd. Porous AAO membrane was purchased from Hefei Jinghui Nanotechnology Co., Ltd. H NMR spectrum ( 1 H NMR) was recorded by a Bruker Avance III 400MHz spectrometer. Scanning electron microscopy (SEM) images were recorded by a Flex SEM 1000Ⅱ scanning electron microscope. I–V curves were recorded by a Keithley 6487 picoammeter. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0034] Example 1

[0035] Preparation of monodispersed UiO-66-NH2 nanoparticles

[0036] SEM images of monodispersed UiO-66-NH2 nanoparticles are shown in Figure 2. Figure 1 As shown in the figure, it can be seen that UiO-66-NH2 nanoparticles exist in a single dispersed form, and the particle size is 130±30nm.

[0037] Specific process: ZrCl4 (183 mg), 2-aminoterephthalic acid (143 mg) and 45 mL N, N-dimethylformamide (DMF) were mixed in a container. After the mixture was ultrasonicated for 15 minutes until the solid was completely dissolved, glacial acetic acid (1.36 mL) was added to the above mixed solution. After the mixture was stirred for 15 minutes, it was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in an oven at a constant temperature of 120°C for 24 hours. After the reaction was completed, the reactor was allowed to cool naturally to room temperature and then opened. The product was centrifuged (8000 rpm, 10 min), and the obtained solid was washed with DMF and methanol in turn. The washed solid was placed in a vacuum drying oven set at 40°C and dried for 12 hours to obtain the product UiO-66-NH2, whose pore size is The total pore volume is 0.2-0.3cm 3 / g.

[0038] Example 2

[0039] Preparation of cat-CTA

[0040] cat-CTA 1 H NMR spectrum Figure 2 As shown, the chemical shift and integrated area of ​​the corresponding proton absorption peak in cat-CTA can be seen, proving the successful synthesis of cat-CTA.

[0041] Specific process: 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid (1.0 g), N-hydroxysuccinimide (428 mg) and 40 mL of dry dichloromethane were mixed in a reaction bottle. After the reaction bottle was placed in an ice-water bath and stirred for 60 min, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (760 mg) was added, and then the mixture was stirred at room temperature for 12 h. After the reaction was completed, the product was washed with dilute hydrochloric acid (1 M), saturated NaHCO3 and deionized water in turn, and the product in the aqueous solution was extracted with dichloromethane, and then the dichloromethane solution was dried with anhydrous MgSO4 for 20 min. The dried solution was filtered and concentrated to a solution volume of 0.5 mL, and the crude product was purified with a silica gel column (silica gel particle size of 200-300 mesh), and the eluent was a mixed solution of petroleum ether and ethyl acetate with a volume ratio of 2:1 to obtain the product NHS-CTA.

[0042] NSH-CTA (1.0 g), dopamine hydrochloride (417 mg) and 40 mL of dry tetrahydrofuran were mixed in a reaction bottle. After the reaction bottle was placed in an ice-water bath and stirred for 60 min, triethylamine (306 μL) was added, and the mixture was then stirred at room temperature for 12 h. After the reaction was completed, the solvent was dried using a rotary evaporator, the crude product was dissolved in dichloromethane, washed with dilute hydrochloric acid (1 M) and deionized water in turn, the product in the aqueous solution was extracted with dichloromethane, and then the dichloromethane solution was dried with anhydrous MgSO4 for 20 min. The dried solution was filtered and concentrated to a solution volume of 0.5 mL, and the crude product was purified using a silica gel column (silica gel particle size of 200-300 mesh), and the eluent was a mixed solution of petroleum ether and ethyl acetate with a volume ratio of 1:1. The purified product was placed in a vacuum drying oven set at 40 ° C and dried for 12 h to obtain the product cat-CTA.

[0043] Example 3

[0044] UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 )

[0045] UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) Acid hydrolysis products 1 H NMR spectrum Figure 3As shown, the content of imidazole groups in the copolymer was calculated to be about 1 mol % based on the integrated area of ​​the proton peak in the figure.

[0046] Specific process: 1) UiO-66-NH2 (100 mg) obtained in Example 1, cat-CTA (144 mg) obtained in Example 2 and 40 mL DMF were mixed in a reaction bottle, and the mixture was ultrasonicated for 30 min until the solid was completely dispersed. Then the reaction bottle was placed in an oil bath pot with a constant temperature of 100°C for 4 hours. After the reaction was completed, the product was cooled to room temperature, centrifuged (8000 rpm, 10 min), and the obtained solid was washed with DMF and methanol in turn and placed in a vacuum drying oven set at a temperature of 40°C for 12 hours to obtain the product UiO-66-NH2-CTA.

[0047] 2) UiO-66-NH2-CTA (100 mg) was mixed with 100 mL DMF in a container and ultrasonicated for 30 min until the solid was completely dispersed. Then MMA (20 mL), VIM (174 μL) and AIBN (10 mg mL -1 ,76μL). The mixture was frozen with liquid nitrogen for 15min, evacuated with an oil pump (pressure range of 3-5Mpa) for 5min, and then thawed naturally at room temperature; after the above freezing-evacuation-thawing operation cycle was repeated 3 times, the mixture was placed in an oil bath pot at a constant temperature of 70°C for 24h. After the reaction, the crude product was centrifuged (8000rpm, 10min), and the obtained solid was washed with DMF and then with toluene. The product was placed in a vacuum drying oven set at 60°C and dried for 12h to obtain the product UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) (particle size is 160±30nm).

[0048] 3) 20.0 mg of dried U iO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) particles were immersed in a mixed solvent of 500 μL methanol and 6 μL HF solution (48% mass concentration aqueous solution), and then the mixture was subjected to ultrasonic treatment for 20 min. The obtained precipitate was collected by centrifugation (8000 rpm, 5 min), and the obtained solid was washed 3 times with 30 mL methanol, and then washed once with 10 mL toluene, and then placed in a vacuum drying oven set at 60 ° C for 12 h to obtain the acid hydrolysis product P (MMA-co-VIM).

[0049] Example 4

[0050] Preparation of SAMM membrane

[0051] SEM images of SAMM films are shown in Figure 2. Figure 4 As shown, Figure a shows the curled film, and Figure b shows the close arrangement of nanoparticles on the film surface. The calculated film thickness is about 160nm, indicating that the SAMM film is a dense film formed by the close stacking of a single layer of MOF nanoparticles.

[0052] Specific process: 50 mg of UiO-66-NH2-P (MMA) prepared in Example 3 was added 0.99 -co-VIM 0.01 ) nanoparticles were mixed with 1 mL of toluene in a small glass bottle and then ultrasonicated for 40 min to obtain MOF dispersion.

[0053] Take 10 μL of the above MOF dispersion and drop it into a culture dish filled with water with a diameter of 35 mm and a water depth of 1 cm. After leaving it at room temperature for 3 minutes, a SAMM membrane with a diameter of about 30 mm is formed on the water surface.

[0054] Example 5

[0055] Preparation of heterogeneous membranes

[0056] SEM images of AAO and heterogeneous membranes are shown in Figure 5 As shown in the figure, it can be seen that the SAMM membrane in the heterogeneous membrane completely covers the opening of the AAO membrane. The thickness of the upper SAMM membrane is calculated from the cross-sectional SEM image to be about 160nm, which is consistent with the thickness of the single-layer SAMM, indicating that only one layer of SAMM membrane is covered on the AAO substrate. Due to the positive charge of the AAO membrane itself, it has weak osmotic energy conversion performance, so we chose porous AAO as the substrate of the heterogeneous membrane. At the same time, we compared the output power of AAO membranes with different pore sizes under simulated seawater and river water salinity gradients. The specific process is: four porous AAO membranes with different pore sizes (pore size range of 20-30nm (pore density of 1.0×10 12 pores / cm 2 , membrane thickness is 60 μm), 40-70 nm (pore density is 8.0×10 11 pores / cm 2 , membrane thickness is 100 μm), 80-100 nm (pore density is 5.0×10 11 pores / cm 2 , membrane thickness is 100 μm), 110-150 nm (pore density is 1.0×10 11 pores / cm 2 , the membrane thickness is 120μm)) and the central hole area is 0.004mm 2The silicon wafers are stacked together and fixed between the two modules of the current test device (the actual test area is the hole area on the silicon wafer). Corresponding through holes are set on the two modules on both sides of the membrane as flow channels, and one port of the two flow channels is set correspondingly on both sides of the membrane. 1mL of 500mM NaCl solution is added to the flow channel on one side of the AAO membrane, and 1mL of 10mM NaCl solution is added to the flow channel on one side of the silicon wafer. Ag / AgCl electrodes are placed in the electrolyte solutions in the two flow channels, and a scanning voltage varying from -0.2V to +0.2V is applied through the electrodes as the transmembrane potential. A picoammeter is used to record the ion current generated by the solution in the two flow channels. We found that the output power density of the four AAO membranes was 0.37W / m 2 (pore size 20-30nm), 0.12W / m 2 (aperture 40-70nm), 0.10W / m 2 (pore size 80-100nm), 0.09W / m 2 (pore size 110-150nm), so we chose the AAO membrane with relatively better performance (pore size range 20-30nm, pore density 1.0×10 12 pores / cm 2 , membrane thickness is 60 μm) as the substrate and composited with SAMM membrane to prepare heterogeneous membrane.

[0057] Specific process: After the SAMM membrane of Example 4 is formed on the water surface, the AAO membrane is immersed in the water below the SAMM, and slowly moved toward the water surface with one side of the AAO parallel to the water surface until the SAMM completely covers the AAO. The composite membrane is placed in a covered petri dish and dried at room temperature for 24 hours to form a heterogeneous membrane.

[0058] Example 6

[0059] Testing of the osmotic energy collection performance of heterogeneous membranes

[0060] The collected current density and power density curves of the heterogeneous membrane obtained in Example 5 under a 50-fold NaCl gradient and the module schematic diagram in the current test device are shown in FIG. Figure 6 , Figure 7 As shown in the figure, it can be seen that the heterogeneous membrane can generate 215A / m under the salinity gradient of simulated seawater and river water. 2 The maximum current density and 2.99W / m 2 The maximum power density of the membrane was 0.37W / m 2 and 1.59W / m 2By comparison, it was found that compared with the AAO substrate, the output power of the two heterogeneous membranes under a 50-fold NaCl gradient increased, and the power increase of the heterogeneous membrane containing imidazole groups was greater, indicating that the introduction of imidazole groups into the SAMM membrane can further enhance the osmotic energy conversion performance of the heterogeneous membrane.

[0061] Specific process: polymethyl methacrylate (PMMA) was grafted onto the surface of UiO-66-NH2 particles by the method described in Example 3 to prepare UiO-66-NH2-PMMA particles (the particle size was 160±30 nm, and the difference from Example 3 was that VIM was not added in step (2), and only MMA (20 mL) was added as a monomer for polymerization reaction). UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ) nanoparticles are replaced by UiO-66-NH2-PMMA particles of equal mass), and the UiO-66-NH2-PMMA particles are used to form a SAMM film (thickness is about 160nm) at the water-air interface. The SAMM film is further covered on the AAO substrate by the method described in Example 5 to form a heterogeneous membrane (the difference from Example 5 is that the SAMM membrane used is UiO-66-NH2-PMMA particles forming a SAMM film at the water-air interface). Compared with the heterogeneous membrane obtained in Example 5 (SAMM containing imidazole groups), this SAMM does not contain imidazole groups and is tested as a control group. The AAO substrate and the two heterogeneous membranes are respectively connected to a central hole with an area of ​​0.004mm 2 The silicon wafers are stacked together and fixed between the two modules of the current test device (the actual test area is the hole area on the silicon wafer, and the silicon wafer is attached to the AAO membrane side of the heterogeneous membrane). Corresponding through holes are set on the two modules on both sides of the membrane as flow slots, and one port of the two flow slots is set correspondingly on both sides of the membrane. In order to simulate the osmotic energy collection of actual seawater and river water, the salt gradient in the flow slots on both sides is set to 50 times the NaCl solution. For the AAO substrate test, 1mL of 500mM NaCl solution is added to the flow slot on one side of the AAO membrane, and 1mL of 10mM NaCl solution is added to the flow slot on one side of the silicon wafer. For the heterogeneous membrane test, 1mL of 500mM NaCl solution is added to the flow slot on one side of the SAMM, and 1mL of 10mM NaCl solution is added to the flow slot on one side of the silicon wafer. Ag / AgCl electrodes were placed in the electrolyte solutions in the two flow channels respectively, and a scanning voltage varying from -0.2V to +0.2V was applied through the electrodes as the transmembrane potential. A picoammeter was used to record the ion current generated by the solutions in the two flow channels. The short-circuit currents obtained were 0.27μA (AAO substrate), 0.49μA (heterogeneous membrane without imidazole), and 0.86μA (heterogeneous membrane obtained in Example 5).

[0062] The area on a silicon wafer is 0.004mm 2 The through holes serve as the effective test area.

[0063] The current test device is composed of two polytetrafluoroethylene rectangular blocks, one side of which is placed opposite to the other, and a polytetrafluoroethylene cylindrical protrusion (such as Figure 7 The cylindrical protrusions on the two rectangular blocks are arranged opposite to each other, and a circular through hole with an "L"-shaped axis and a diameter of 5mm is provided between the end face of the cylindrical protrusion and the upper surface of the rectangular block where the cylindrical protrusion is located, which serves as a flow channel (volume is 1.2mL). The circular through hole ports on the two cylindrical protrusions are arranged opposite to each other, and two through holes C connecting the upper surface and the circular through holes are provided vertically downward on the upper surfaces of the two rectangular blocks, which serve as pressure balance grooves. The membrane to be treated or tested is clamped between the cylindrical protrusions of the two rectangular blocks, and both sides of the membrane are sealed and attached to the surfaces of the cylindrical protrusions of the two rectangular blocks, and the circular through hole ports on the cylindrical protrusions are arranged opposite to each other on both sides of the membrane.

[0064] In summary, the present invention designs and prepares a positively charged MOF monolayer film formed by self-assembly of MOF nanoparticles coated with functional polymers. This type of film is a monolayer film formed by evaporation-induced self-assembly of MOF particles at the water-air interface. It is a very dense (MOF particles are tightly and closely arranged) and extremely thin (~160nm) film. The prepared SAMM membrane is combined with a porous AAO membrane to prepare a positively charged heterogeneous membrane, which exhibits efficient osmotic energy collection performance. This invention not only provides a new method for preparing functionalized SAMM membranes, but also provides a new idea for preparing ion exchange membrane materials with efficient osmotic energy collection.

[0065] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a positively charged heterogeneous membrane, characterized in that: The method is formed by combining a positively charged self-assembled metal organic framework (MOF) monolayer (SAMM) membrane with a porous anodic aluminum oxide (AAO) membrane. The specific steps are as follows: After the SAMM membrane is formed at the water-air interface, the AAO membrane is immersed in water below the SAMM membrane and then moved toward the water surface with one side surface of the AAO membrane facing the water surface until the SAMM membrane covers one side surface of the AAO to form a composite membrane.

2. The preparation method according to claim 1, characterized in that: The composite film is placed in a covered culture dish and dried at room temperature for 12-24 hours (preferably 15-22 hours, more preferably 18-20 hours) to obtain a positively charged heterogeneous film; The porous AAO membrane has a pore size of 20-70 nm (preferably 20-50 nm, more preferably 20-30 nm) and a pore density of 0.1×10 12 -1.5×10 12 pores / cm 2 (Preferably 0.5×10 12 -1.5×10 12 pores / cm 2 , more preferably 1.0×10 12 -1.2×10 12 pores / cm 2 ).

3. The preparation method according to claim 1, characterized in that: The SAMM membrane is formed by self-assembly of MOF nanoparticles coated with functional polymers at the water-air interface, and the specific steps are as follows: (1) 30-100 mg (preferably 40-80 mg, more preferably 50-60 mg) of UiO-66-NH2 (expressed as UiO-66-NH2-P(MMA)) coated with a functional polymer 0.99 -co-VIM 0.01 )) The nanoparticles are mixed with 0.7-1.2 mL (preferably 0.8-1.1 mL, more preferably 0.9-1.0 mL) of toluene in a container, and then ultrasonicated for 30-60 min (preferably 35-55 min, more preferably 40-50 min) to obtain a MOF dispersion; (2) Take 10-15 μL (preferably 10-13 μL, more preferably 10-11 μL) of the MOF dispersion prepared in step (1), drop it into water in a culture dish with an internal cavity diameter ≥30 mm (preferably ≥35 mm) and a water depth >300 nm (preferably >1 cm), and place it at room temperature for 1-6 min (preferably 2-5 min, more preferably 3-4 min) until toluene is completely evaporated, and a SAMM film with a thickness equal to the particle size of the nanoparticles formed by a single layer of nanoparticles is formed on the water surface.

4. The preparation method according to claim 3, characterized in that: The UiO-66-NH2-P(MMA) in step (1) 0.99 -co-VIM 0.01 ) is to graft the functional polymer onto the surface of UiO-66-NH2 particles through a surface reversible addition-fragmentation chain transfer (RAFT) polymerization reaction initiated by methyl methacrylate (MMA) and 1-vinylimidazole (VIM). The specific steps are as follows: (1) The macromolecular chain transfer agent modified UiO-66-NH2 (expressed as UiO-66-NH2-CTA, 95-105 mg, preferably 97-103 mg, more preferably 99-101 mg) and 95-105 mL (preferably 97-103 mL, more preferably 99-101 mL) of DMF were mixed in a container, and then MMA (10-40 mL, preferably 15-30 mL, more preferably 20-25 mL), VIM (100-300 μL, preferably 120-250 μL, more preferably 150-200 μL), 2,2'-azobisisobutyronitrile (AIBN, 10 mg mL -1 , 50-100 μL, preferably 60-90 μL, more preferably 70-80 μL); (2) freezing the mixture in step (1) with liquid nitrogen for 10-20 min (preferably 12-18 min, more preferably 14-16 min), evacuating with an oil pump (pressure range of 1-10 MPa, preferably 2-8 MPa, more preferably 3-5 MPa) for 1-10 min (preferably 2-8 min, more preferably 4-6 min), and then thawing the mixture naturally at room temperature; after the above freezing-evacuation-thawing operation is cycled 2-5 times, placing the mixture in an oil bath pot at a constant temperature of 60-100° C. (preferably 70-90° C., more preferably 70-80° C.) to react for 18-26 h (preferably 19-25 h, more preferably 20-24 h); (3) After the reaction is completed, the crude product is centrifuged (7000-10000 rpm, 10-20 min, preferably 7500-9000 rpm, 12-18 min, more preferably 8000-8500 rpm, 14-16 min), and the resulting solid is washed with DMF and then with toluene; (4) The solid washed in step (3) is dried at 50-80° C. (preferably 55-70° C., more preferably 60-65° C.) for 10-15 h (preferably 11-14 h, more preferably 12-13 h) to obtain the product UiO-66-NH2-P(MMA 0.99 -co-VIM 0.01 ), the particle size is 160±30nm.

5. The preparation method according to claim 4, characterized in that: UiO-66-NH2-CTA is prepared by post-synthesis modification of UiO-66-NH2 and a macromolecular chain transfer agent (cat-CTA), and the specific steps are as follows: UiO-66-NH2 (95-105 mg, preferably 97-103 mg, more preferably 99-101 mg), cat-CTA (100-180 mg, preferably 120-160 mg, more preferably 140-150 mg) and 30-60 mL (preferably 35-55 mL, more preferably 40-50 mL) of DMF were mixed in a reaction bottle, and the mixture was ultrasonicated for 20-60 min (preferably 30-50 min, more preferably 30-40 min) until the solid was completely dispersed; then the reaction bottle was kept at a constant temperature of 90-120 ° C (preferably 90-110 ° C, more preferably 100-110 ° C) for reaction 3-6h (preferably 4-6h, more preferably 4-5h); after the reaction is completed, the product is cooled to room temperature, the product is centrifuged (7000-10000rpm, 10-20min, preferably 7500-9000rpm, 12-18min, more preferably 8000-8500rpm, 14-16min), the obtained solid is washed with DMF and methanol in sequence, and then placed in a vacuum drying oven set at a temperature of 30-60°C (preferably 35-50°C, more preferably 40-45°C) and dried for 10-15h (preferably 11-14h, more preferably 12-13h) to obtain the product UiO-66-NH2-CTA.

6. The preparation method according to claim 5, characterized in that: The preparation of monodispersed UiO-66-NH2 nanoparticles and cat-CTA, the specific steps are as follows: Preparation of monodisperse UiO-66-NH2 nanoparticles: ZrCl4 (160-210 mg, preferably 170-200 mg, more preferably 180-190 mg), 2-aminoterephthalic acid (120-170 mg, preferably 130-160 mg, more preferably 140-150 mg) and 30-60 mL (preferably 35-55 mL, more preferably 40-50 mL) of DMF were mixed in a container; the mixture was ultrasonicated for 5-30 min (preferably 10-25 min, more preferably 15-20 min) until the solid was completely dissolved; then, glacial acetic acid (1.0-2.0 mL, preferably 1.1-1.8 mL, more preferably 1.3-1.5 mL) was added to the above mixed solution and stirred for 5-30 min (preferably 10-25 min, more preferably 15-20 min); the mixture was transferred to an autoclave. , placed in an oven at a constant temperature of 100-140°C (preferably 110-130°C, more preferably 120-130°C) for reaction for 20-30h (preferably 22-28h, more preferably 23-25h); after the reaction, the reactor is allowed to cool naturally to room temperature and then opened, the product is centrifuged (7000-10000rpm, 10-20min, preferably 7500-9000rpm, 12-18min, more preferably 8000-8500rpm, 14-16min), and the obtained solid is washed with DMF and methanol in turn; the washed solid is placed in a vacuum drying oven set at a temperature of 30-60°C (preferably 35-50°C, more preferably 40-45°C) and dried for 10-15h (preferably 11-14h, more preferably 12-13h) to obtain the product UiO-66-NH2, with a particle size of 130±30nm.

7. The preparation method according to claim 5, characterized in that: The preparation of cat-CTA, the specific steps are as follows: Preparation of cat-CTA: 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid (0.8-1.2 g, preferably 0.9-1.2 g, more preferably 0.9-1.1 g), N-hydroxysuccinimide (400-440 mg, preferably 410-440 mg, more preferably 420-430 mg) and 30-60 mL (preferably 35-55 mL, more preferably 40-50 mL) of dry dichloromethane are mixed in a reaction flask; the reaction flask is placed in an ice-water bath and stirred for 30-60 min (preferably 40-60 min, more preferably 40-50 min), and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (700-800 mg, preferably 720-780 mg, more preferably 430-440 mg) is added. Preferably 750-770 mg); the mixture is stirred at room temperature for 10-15 h (preferably 11-14 h, more preferably 12-13 h); after the reaction is completed, the product is washed with dilute hydrochloric acid (0.5-2.0 M, preferably 1.0-2.0 M, more preferably 1.0-1.5 M), saturated NaHCO3 and deionized water in sequence, the product in the aqueous solution is extracted with dichloromethane, and then the dichloromethane solution is dried with anhydrous MgSO4 for 10-40 min (preferably 15-30 min, more preferably 20-25 min); the dried solution is filtered and concentrated, and the crude product is purified by a silica gel column, and the eluent is a mixed solution of petroleum ether and ethyl acetate in a volume ratio of 1:1-5:1 (preferably 1:1-4:1, more preferably 2:1-3:1); The above pure product (0.8-1.2g, preferably 0.9-1.2g, more preferably 0.9-1.1g), dopamine hydrochloride (400-430mg, preferably 410-430mg, more preferably 410-420mg) and 30-60mL (preferably 35-55mL, more preferably 40-50mL) of dry tetrahydrofuran are mixed in a reaction flask; the reaction flask is placed in an ice water bath and stirred for 30-60min (preferably 40-60min, more preferably 40-50min), and triethylamine (280-320μL, preferably 290-310μL, more preferably 300-310μL) is added; the mixture is placed at room temperature and stirred for 10-15h (preferably 11-14h, more preferably 12-13h); after the reaction is completed, the solvent is dried by rotary evaporator, and the crude product is dissolved in dichloromethane. , sequentially washed with dilute hydrochloric acid (0.5-2.0M, preferably 1.0-2.0M, more preferably 1.0-1.5M) and deionized water, the product in the aqueous solution was extracted with dichloromethane, and then the dichloromethane solution was dried over anhydrous MgSO4 for 10-40min (preferably 15-30min, more preferably 20-25min); the dried solution was filtered and concentrated, and the crude product was purified by a silica gel column, and the eluent was a mixed solution of petroleum ether and ethyl acetate in a volume ratio of 1:1-4:1 (preferably 1:1-3:1, more preferably 1:1-2:1); the purified product was placed in a vacuum drying oven set at a temperature of 30-60°C (preferably 35-50°C, more preferably 40-45°C) and dried for 10-15h (preferably 11-14h, more preferably 12-13h) to obtain the product cat-CTA.

8. A positively charged heterogeneous membrane prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the heterogeneous membrane according to claim 8, characterized in that: Applied to the collection of osmotic energy between salt water (such as salt water, preferably sea water) and water (such as river water).

10. The preparation method according to claim 9, characterized in that: Use an electrochemical device to collect osmotic energy, and use a picoammeter to record the ion current generated by the solution in the second flow cell. The specific steps are as follows: The heterogeneous membrane and the silicon wafer are fixed together between two modules of the electrochemical device, and corresponding through holes are respectively arranged on the two modules on both sides of the heterogeneous membrane as flow channels, one port of the two flow channels is correspondingly arranged on both sides of the heterogeneous membrane, and the through hole on the silicon wafer between the two corresponding flow channel ports is the actual test area; A 300-800 mM (preferably 400-700 mM, more preferably 500-600 mM) NaCl solution is added to the flow channel on the SAMM side, and an 8-13 mM (preferably 9-12 mM, more preferably 10-11 mM) NaCl solution is added to the flow channel on the AAO side; Ag / AgCl electrodes are placed in the electrolyte solutions in the two flow channels respectively, and a scanning voltage varying from -0.4 V to +0.4 V (preferably -0.3 V to +0.3 V, more preferably -0.2 V to +0.2 V) is applied through the electrodes as the transmembrane potential, and a picoammeter is used to record the corresponding current value.

Citation Information

Patent Citations

  • Method for preparing novel mixed matrix nanofiltration membrane of polyelectrolyte / metal organic framework compound by using layer-by-layer self-assembly method

    CN108579423A

  • Single-particle-layer metal organic framework mixed matrix nano-porous membrane and preparation method thereof

    CN116328559A

  • Polyvinylidene fluoride membrane

    GB9424308D0

  • Membranes comprising a layer of metal organic framework particles

    US20210016232A1

  • System AMD methods for the removal of soft heavy metals from streams

    WO2009002915A1